Activated Carbon-Limestone-Alginate (Ala) Beads For The Removal Of Colour And Turbidity From Kerian River Water - Rosli, Nur Athirah (Universiti Sains Malaysia, 2019)
This study focused on the usage of activated carbon (AC), limestone (LS) and alginates in treating the Kerian river water. Therefore, the best mix ratio (AC: LS) 3:7 has been adapted based on the previous study to produced composite adsorbent for removal of colour and turbidity and followed by regeneration of the used composite adsorbent. Factor of adsorbent dosage, contact time and shaking speed were considered for optimization processes to get maximum value for the removal of colour and turbidity of the river water. As a result, the composite adsorbent manages to remove 94.15% colour and 90.92% turbidity by using optimum adsorbent dosage settings of 23.14 g, shaking speed of 114rpm and contact time of 71min. Kinetic and isotherm adsorption model for composite adsorbent were also determined. The result shows that the maximum adsorption capacity of one layer composite adsorbent for colour and turbidity are 17.857 PtCo/g and 8.078 NTU/g, respectively. Meanwhile, the kinetic adsorption model describes the suitability of the use of pseudo-second order. Freundlich isotherm is suitable for equilibrium adsorption data. Regeneration of adsorbent is done by solvent wash method by using methanol but unfortunately the removal of colour and turbidity of river water was not successful which it brings negative value.